2018
DOI: 10.1186/s13063-018-3050-4
|View full text |Cite|
|
Sign up to set email alerts
|

Dexamethasone for adult patients with a symptomatic chronic subdural haematoma (Dex-CSDH) trial: study protocol for a randomised controlled trial

Abstract: BackgroundChronic subdural haematoma (CSDH) is a common neurosurgical condition, typically treated with surgical drainage of the haematoma. However, surgery is associated with mortality and morbidity, including up to 20% recurrence of the CSDH. Steroids, such as dexamethasone, have been identified as a potential therapy for reducing recurrence risk in surgically treated CSDHs. They have also been used as a conservative treatment option, thereby avoiding surgery altogether. The hypothesis of the Dex-CSDH trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…9 However, ongoing RCTs are investigating the value of corticosteroids as stand-alone and adjacent treatment to surgery for CSDH. 13,14 A recent placebo-controlled RCT showed that atorvastatin significantly lowers hematoma volume and neurological symptoms as a stand-alone treatment of cSDH. 15 Hence, atorvastatin could be considered a pharmacological treatment, especially for geriatric patients who are often highrisk surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, ongoing RCTs are investigating the value of corticosteroids as stand-alone and adjacent treatment to surgery for CSDH. 13,14 A recent placebo-controlled RCT showed that atorvastatin significantly lowers hematoma volume and neurological symptoms as a stand-alone treatment of cSDH. 15 Hence, atorvastatin could be considered a pharmacological treatment, especially for geriatric patients who are often highrisk surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
“…26 Current studies examining strategies to decrease risk of recurrence include the Swedish study of irrigation-fluid temperature in the evacuation of CSDH (SIC! ), 27 the Dutch dexamethasone therapy versus surgery for CSDH (DECSA trial), 28 the British dexamethasone for adult patients with a symptomatic CSDH trial, 29 and two Canadian studies looking at the role of tranexamic acid in the treatment of CSDHs (TRACS trial, NCT02568124 30 and TRACE trial, NCT03280212).…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] This dose and duration are similar to other studies currently ongoing in TBI patients. [ 9 , 10 ]…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless based on the experience with patients with brain tumors, dexamethasone is commonly administered to patients undergoing a variety of neurosurgical procedures, [ 8 ] and is currently under investigation in specific subgroups of TBI patients like patients with chronic subdural hematomas. [ 9 , 10 ] Among the groups of patients that occasionally receive dexamethasone are patients with brain contusions and pericontusional edema where steroids are believed to improve the vasogenic component.…”
Section: Introductionmentioning
confidence: 99%